2004
DOI: 10.1080/09153590400007317
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inducible nitric oxide synthase messenger RNA, but not guanylate cyclase messenger RNA, depends on gestational age in rat myometrium

Abstract: We studied the expression of inducible nitric oxide (NO) synthase (iNOS) and soluble guanylate cyclase (sGC) mRNAs in pregnant rat myometrium. Expression of iNOS and sGC alpha1, beta1 and beta2 mRNA was analyzed in non-pregnant and pregnant (days 10, 14, 17 and 21) Wistar rats by reverse transcription-polymerase chain reaction. Expression of iNOS mRNA increased during pregnancy but decreased on day 21 of gestation. Expression of GC alpha1 mRNA was greater than GC beta1 mRNA at all time points. Expression of ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our data show a 10‐fold increase in mRNA for iNOS during pregnancy followed by a marked decline at the time of uterine activation, concurrent with the increase in expression of mRNA for OTR. This confirms previous findings for iNOS in the uterus of both rat and human (Ali et al 1997; Bansal et al 1997; Okawa et al 2004; Mitchell et al 2005). These findings are in agreement with the concept (Lopez Bernal et al 1995) that the process of uterine activation includes not only increased expression of uterine contractile systems but also a repression of uterine relaxant systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data show a 10‐fold increase in mRNA for iNOS during pregnancy followed by a marked decline at the time of uterine activation, concurrent with the increase in expression of mRNA for OTR. This confirms previous findings for iNOS in the uterus of both rat and human (Ali et al 1997; Bansal et al 1997; Okawa et al 2004; Mitchell et al 2005). These findings are in agreement with the concept (Lopez Bernal et al 1995) that the process of uterine activation includes not only increased expression of uterine contractile systems but also a repression of uterine relaxant systems.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, during pregnancy in both the rat and human, the endometrium expresses the enzyme inducible nitric oxide synthase (iNOS), which produces nitric oxide, a smooth muscle relaxant (Buhimschi et al 1995, 1996; Bansal et al 1997; Okawa et al 1998). In contrast to the CAPs, rat uterine concentrations of mRNA encoding iNOS decrease prior to parturition (Okawa et al 2004; Mitchell et al 2005).…”
mentioning
confidence: 95%
“…iNOS is present in the cervix of many different species during pregnancy and increases during labour, suggesting a role for NO in the ripening process and parturition (2,14). Furthermore, during pregnancy in both rats and humans, endometrium expresses the enzyme iNOS which is a smooth muscle relaxant (4,19). Buhimschi et al investigated the presence and gestational differences in NOS isoforms in the rat uterus versus the cervix and concluded that only iNOS and eNOS were present in the uterus during pregnancy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that there may be an interaction between NO and PG pathways in regulating the NOS and COX expression and this interaction may play a critical role in the control of cervical ripening and parturition (25,30). In addition, it has been shown that during pregnancy in both the rat and human, the endometrium expresses the enzyme iNOS, which produces nitric oxide, a smooth muscle relaxant (4,19).…”
Section: Introductionmentioning
confidence: 99%